High temperature laser diode based on a single sheet of quantum dots. (11th August 2015) - Ledentsov, N N; Shchukin, V A; Maximov, M V; Shernyakov, Yu M; Payusov, A S; Gordeev, N Yu; Rouvimov, S S
Abstract: A single sheet of high-density InGaAs quantum dots (QDs) is used as a gain medium of InGaAs–GaAs–AlGaAs lasers. The devices operate at high power in the continuous mode beyond 160 °C with an emission wavelength up to ∼1.27 μ m. At short cavity lengths a strong broadening (>300 nm) of the electroluminescence spectrum is observed at high current densities, permitting light sources for broadly wavelength tuneable and multi-wavelength infrared lasers based on a single gain chip, and related frequency conversion devices for the whole visible spectrum range. High power cw operation (>2 W) limited by catastrophic optical mirror damage is realized.